1962
DOI: 10.1111/j.1476-5381.1962.tb01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drugs on the Noradrenaline Content of Brain and Peripheral Tissues and Its Significance

Abstract: Large single doses of methoserpidine (12 mg/kg) given to rabbits lowered the noradrenaline content of sympathetic ganglia but not that of brain; no sedation was observed. Cats responded to doses ranging from 12 to 0.5 mg/kg with loss of noradrenaline from ganglia as well as from brain, and were sedated by the drug. The effect in man resembles that in the rabbit. Only within the group of reserpine-like drugs do sedation and loss in hypothalamic noradrenaline run parallel. These effects are therefore not causall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1

Year Published

1962
1962
1977
1977

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 22 publications
2
24
1
Order By: Relevance
“…Thus, the pressor potency was reduced by treatment with the catecholamine depleting substances, reserpine and syrosingopine, and was restored by infusions of catecholamines. Similarly, inhibition of monoamine oxidase which has been shown to increase peripheral levels of catecholamines (Goldberg & Shideman, 1962;Sanan & Vogt, 1962) (Feldberg & Lewis, 1964, 1965Vane, 1969 (Bickerton & Buckley, 1961) and via central vagal inhibition (Scroop & Lowe, 1968). The failure of both pempidine and bethanidine to reduce the angiotensin pressor responses in the present experiments argues against a significant central component to the response.…”
contrasting
confidence: 39%
“…Thus, the pressor potency was reduced by treatment with the catecholamine depleting substances, reserpine and syrosingopine, and was restored by infusions of catecholamines. Similarly, inhibition of monoamine oxidase which has been shown to increase peripheral levels of catecholamines (Goldberg & Shideman, 1962;Sanan & Vogt, 1962) (Feldberg & Lewis, 1964, 1965Vane, 1969 (Bickerton & Buckley, 1961) and via central vagal inhibition (Scroop & Lowe, 1968). The failure of both pempidine and bethanidine to reduce the angiotensin pressor responses in the present experiments argues against a significant central component to the response.…”
contrasting
confidence: 39%
“…It is ur'ilikely, in our opinion, that this was the result of a reflex mechanism, as was suggested by Sanan & Vogt (1962) to account for the small but significant decrease in the hypo-thalamic concentration of noradrenaline which they observed in rabbits treated with guanethidine. In the rabbit both guanoxan and guanethidine decreased the noradrenaline levels in peripheral tissues.…”
Section: Discussionmentioning
confidence: 72%
“…Some biochemical studies have shown that high doses of amphetamine can lower the concentration of endogenous brain noradrenaline (McLean & McCartney, 1961;Moore & Lariviere, 1963;Baird & Lewis, 1964;Smith, 1965;Leonard & Shallice, 1971) but other studies have produced differing results (Sanan & Vogt, 1962;Breese, Kopin & Weise, 1970;Simon, Tillement, Larousse, Breteau, Guernet & Boissier, 1970). The significance of these findings is not clear as the doses of amphetamine used in these studies were in the lethal range (Stolk & Rech, 1968).…”
Section: Resultsmentioning
confidence: 99%